Self‐assessed health status changes in a community cohort of people with multiple sclerosis: 11 years of follow‐up. Issue 4 (6th December 2012) - Giordano, A.; Ferrari, G.; Radice, D.; Randi, G.; Bisanti, L.; Solari, A.
<x xml:space="preserve">Abstract</x> Background and purpose Few data are available on the health status of people with multiple sclerosis (PwMS) in the community. We assessed changes in self‐perceived health status and health related quality of life of a community‐based cohort of PwMS over a decade, and identified predictors of such changes. Methods In 1999 we started the POSMOS study (Postal Survey of Self‐Assessed Health of MS Adults and their Significant Others) on a random sample of 251 adults with MS from the Milan area (mean age 42 years, range 18–71 years), and prospectively assessed changes in self‐perceived health status over 11 years. Participants completed the Multiple Sclerosis Quality‐of‐Life‐54 (MSQOL‐54) and a general/clinical questionnaire. We re‐assessed the cohort in 2004 and 2010, sending the same questionnaires plus the Chicago Multiscale Depression Inventory. Results There were 205 (86%) respondents in 2004, 171 (74%) in 2010; 28 (11%) died during the study. Severely impaired [self‐determined Expanded Disability Status Scale (EDSS) > 6.5] increased from 19% to 32%. One‐fifth remained fully ambulatory (EDSS < 4.0): 25% women (median age 44 years [interquartile range, IQR 39–53], median years from diagnosis 16 [IQR 12–19]); and 17% men (median age 40 years [IQR 38–45], median years from diagnosis 14 [IQR 12–17]). Changes in MSQOL‐54 composite scores were negligible; but among individual scales, change in health, cognitive function and general health worsened, and social function and emotional wellbeing improved significantly. Depressive symptoms were high and stable. Conclusions Multiple sclerosis had a pervasive but inhomogeneous impact on the lives of our MS sufferers. Notwithstanding overall clinical deterioration and aging, hospital admissions and medical consultations decreased, suggesting reduced use of health care resources. By contrast, housing adaptations and home care increased, psychological burden was high and self‐perceived cognitive functioning worsened.